Deciphering Ireland’s Macroeconomic Imbalance Indicators: Statistical Considerations - Cussen, Mary (The Economic and Social Review, 2015)
The recent financial crisis has highlighted the importance of the early detection and correction of macroeconomic vulnerabilities. This has led the European Commission to develop the Macroeconomic Imbalance Procedure (MIP). Under the MIP, the potential vulnerabilities of EU countries are assessed using standard indicators relating to internal and external macroeconomic imbalances. These indicators, however, assume cross-country data are comparable, despite economic and financial structures being very heterogeneous. This is not the case. This paper finds that for countries with substantial international investment, such as Ireland, five of the eleven indicators are materially distorted by financial and non-financial multinational activities. This paper disaggregates these five affected indicators into multinational and indigenous Irish components, insofar as the existing data allows. It finds that for Ireland the MIP indicators underestimate some external imbalances, significantly overestimate private sector credit imbalances and underestimate the deleveraging of the financial sector. Adjusting the indicators to allow for country-specific factors can help diagnose the underlying imbalance, while reducing instances of the MIP highlighting false positives.